ANALISIS POLA MIGRASI DAN KONSUMSI RUMAH TANGGA DI DAERAH ASAL MIGRASI TERKAIT KEMISKINAN DAN KERENTANAN PANGAN (STUDI KASUS INDRAMAYU) - Saptanto, Subhechanis; Lindawati, Lindawati; Zulham, Armen (LPPM Universitas Terbuka, 2011)
Migration is one of the phenomena related social welfare. People tend to migrate to increase their income for better life. This research aims to observe the migration type in coastal area related to poverty and food security, to identify its determinant, to identify the impact of migration activities, and to research the relationship between dynamics of urban-rural labor and capital flow from two areas (urban and rural) and to study the effect of migration to income re-distribution and push the economic growth in coastal areas that caused reducing poverty and gaining better food quality. This research used descriptive statistics method and the primary data was collected by interviewing respondents in Indramayu sampling areas (Eretan Wetan. Eretan Kulon, Dadap and Ilir village). The result shows that in the origin area of migration, type of migration was monthly migration. The cause of migration were resource accessibility, productive asset ownerships, and rural economic growth. In general, by this type of migration, social welfare condition of people in Indramayu sampling areas was in better condition.